1982
DOI: 10.1136/hrt.48.2.140
|View full text |Cite
|
Sign up to set email alerts
|

Acute electrophysiological effects of flecainide acetate on cardiac conduction and refractoriness in man.

Abstract: SUMMARY The electrophysiological effects of flecainide acetate (2 mg/kg as an intravenous infusion over five minutes) were assessed in 47 patients undergoing electrophysiological study. Seven patients had normal electrophysiology, 16 had a direct accessory atrioventricular pathway, 12 had dual atrioventricular nodal (AH) pathways, five had paroxysmal ventricular tachycardia, six had conduction system disease, and one patient had a left atrial tachycardia.No significant change occurred in sinus cycle length. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
3

Year Published

1985
1985
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(40 citation statements)
references
References 21 publications
2
35
0
3
Order By: Relevance
“…Our study identified no flecainide‐induced changes in aERP, indicating that flecainide did not have an influence on atrial repolarization at the chosen stimulation rates. Depending on the model, flecainide has been reported to have variable effects on aERP in vivo 16, 17, 18, 19, 20. In humans, some reported a slight but not significant flecainide‐induced increase in aERP, whereas others reported significant and use‐dependent increases 20, 34.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study identified no flecainide‐induced changes in aERP, indicating that flecainide did not have an influence on atrial repolarization at the chosen stimulation rates. Depending on the model, flecainide has been reported to have variable effects on aERP in vivo 16, 17, 18, 19, 20. In humans, some reported a slight but not significant flecainide‐induced increase in aERP, whereas others reported significant and use‐dependent increases 20, 34.…”
Section: Discussionmentioning
confidence: 99%
“…QRS durations were measured as a surrogate for the effect of flecainide on ventricular conduction velocity, and our results were in agreement with results reported by others 1, 2. Because of sodium channel blockade, and hence depressant effects on cardiac conduction, a flecainide‐induced widening of QRS was expected 20, 40. In humans, recommendations are that flecainide treatment should be discontinued if QRS prolongation exceeds 25% of baseline 36, 41.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Although its effect on refractoriness in normal tissue is relatively small, flecainide significantly prolongs the refractory period of accessory pathways,8 making this a particularly effective agent in the treatment of reentrant tachycardias that use such tissues.…”
Section: Linical and Experimental Studies Have Shown Thatmentioning
confidence: 99%
“…Flecainide, a new class 1C antiarrhythmic agent is an effective broad spectrum anti-arrhythmic (Hellestrand et al, 1982;Hodges et al, 1982;Anderson et al, 1981;Duff et al, 1981;Duran et al, 1982;Anderson et al, 1984). In common with other class 1 agents it induces mild depression of cardiac function in stable coronary artery disease (Legrand et al, 1983;Serruys et al, 1983;Josephson et al, 1984).…”
Section: Introductionmentioning
confidence: 99%